An Introduction to the Teaching Reform of Data Science Courses in the Context of Big Data - Shang Du; Su Shuai (SHS Web of Conferences)
In the big data age, it’s imperative for data science courses to undergo transformation and embrace innovation. Building upon the foundation of existing data science education, we should introduce a big data-informed perspective for curriculum reform. This reform should encompass specific strategies and measures across various dimensions, including curriculum content, pedagogical approaches, theoretical instruction, and practical application scenarios. The goal of this curriculum overhaul is to foster an integration of modern statistical techniques with big data analytics, balancing theoretical knowledge with hands-on experience. It aims to develop students’ statistical acumen and their ability to manage complex datasets within the big data landscape. By doing so, it seeks to elevate students’ overall proficiency and empower them with the skills to apply contemporary mathematical and statistical methods to tackle realworld challenges effectively.